INTERETHNIC RELATIONS IN THE TRANS-BAIKAL TERRITORY: CURRENT STATE AND DEVELOPMENTAL TRENDS (BASED ON THE MATERIALS OF SOCIOLOGICAL STUDY) - Victoria N. Lavrikova (Russian Studies in Culture and Society)
Purpose. The article deals with the issues of interethnic relations as the object of sociological analysis, it also shows the specifics of the study of this type of relations in sociology. The author aims at sociological analysis of interethnic relations in such a multiethnic region as the Trans-Baikal Territory which is characterized by the heterogeneity of its national composition.